A Case of Acute Infantile Hemorrhagic Edema Confused with Child Abuse - Muhammet Bir; Öner Özdemir; Ümmügülsüm Dikici; Ceren Naz Yolaçık (Çocuk Dergisi)
Acute infantile hemorrhagic edema (AIHE) is a type of leukocytoclastic vasculitis with a generally good prognosis and is observed in infants aged 4-24 months. It may be difficult to diagnose in some cases because its clinical findings are similar to those of many other diseases. Trauma and child abuse are among the differential diagnoses and should be first excluded. Although the exact cause of this disease is not known, it has been associated with infections, vaccines, and medications. Staphylococci, Streptococcus, and Adenovirus are the leading infective agents, while many other agents, such as Escherichia coli and Mycobacteria, have been suggested to be the cause of AIHE. Typically, purpuric skin lesions, edema, and fever are the presenting findings. Herein, we report the occurrence of the disease in a 6-month-old girl within a short period after vaccination.